Identity and space on the borderland between old and new in Shanghai: A case study - Deljana Iossifova (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
China's urban geography has been dramatically altered over the past three decades. The co-presence of splinters in urban fabric - contrasting and continuously changing in terms of condition, use, and socio-cultural consistency - is symptomatic for the country's contemporary transition, suspending existing spatial and temporal disconnections particularly on the borderland in-between old and new, poor and rich, traditional and modern. Focusing on three urban groups (long-term urban residents, rural newcomers, and urban newcomers) in a district of sociospatial diversity in Shanghai, this paper examines trajectories of urban restructuring, aspects of sociospatial identification, and elements of the person-environment-relationship.
Keywords: R26; R23; Z19; 330; Shanghai; intraurban borderland; urban restructuring; rural-to-urban migration; coexistence; multiple identity; spatial identity